Broadband Bidirectional and Multi-Channel Unidirectional Acoustic Insulation by Mode-Conversion Phased Units - Chen, Jia-he; Qian, Jiao; Guan, Yi-jun; Ge, Yong; Yuan, Shou-qi; Sun, Hong-xiang; Lai, Yun; Liu, Xiao-jun (Frontiers in Materials, 2021)
The technique of sound insulation has a wide range of potential applications in environment noise control and architectural acoustics. The rapid development of acoustic artificial materials has provided alternative solutions to design sound insulation structures. However, the realization of single-layer planar structures with bidirectional acoustic insulation (BAI) and unidirectional acoustic insulation (UAI) still poses a challenge. Here, we report the theoretical and experimental realization of two types of single-layer phased array lenses which presents the characteristics of broadband BAI and multi-channel UAI. Both types of lenses consist of 12 mode-conversion phased units which are composed of two types of unit cells (I and II) with an opposite phase and a step waveguide. Based on the phase regulation, the designed phased unit can realize the mode conversion between the zero-order and first-order waves and asymmetric sound manipulation, which enables multi-functional sound insulations. Based on the desired theoretical phase profiles, two types of lenses with BAI and UAI are realized for the incidence of the zero-order wave, and their fractional bandwidths can reach about 0.28 and 0.37, respectively. More interestingly, the UAI effect can be reversed for the incidence of the first-order wave. The proposed lenses based on the mode-conversion phased units have the advantages of single-layer planar structure, multi-functional sound insulation, and broad bandwidth, which have wide application prospect.